2009
DOI: 10.4025/actascianimsci.v31i2.4305
|View full text |Cite
|
Sign up to set email alerts
|

Produção e composição químico-bromatológica de duas cultivares de braquiária adubadas com nitrogênio e sua relação com o índice SPAD

Abstract: O estudo foi conduzido com o objetivo de se avaliar a produção de matéria seca da parte aérea (PMSA) e da raiz (PMSR), a composição bromatológica, o teor de clorofila (valor SPAD), assim como se realizar uma análise de correlação entre o teor de clorofila (índice SPAD) e o teor de nitrogênio na planta e produção de matéria seca da parte aérea de duas cultivares de braquiária. O ensaio foi conduzido em esquema fatorial 4 x 2, sendo quatro doses de N (0, 75, 150 e 225 mg dm-3 de N) e duas cultivares de braquiári… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
14

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 1 publication
0
15
0
14
Order By: Relevance
“…Viana et al (2014) of nitrogen, respectively, and according to Maranhão et al (2009), the chlorophyll content, in addition to indirectly measuring the nitrogen status of plants, may also be used as an indicator of the crude protein content of marandu grass. In the interaction of the cuts within each treatment, the highest values for chlorophyll index were observed in the first cut in all treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Viana et al (2014) of nitrogen, respectively, and according to Maranhão et al (2009), the chlorophyll content, in addition to indirectly measuring the nitrogen status of plants, may also be used as an indicator of the crude protein content of marandu grass. In the interaction of the cuts within each treatment, the highest values for chlorophyll index were observed in the first cut in all treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Vitória, esta mesma elevação é menor e igual a 0,0342% (Figura 3). Avaliando a produção e composição químico-bromatológica de duas cultivares de braquiária, verificaram que houve incrementos significativos dos teores protéicos com o aumento das doses de N (Maranhão et al, 2009 Os teores de FDA constituem-se em um fator de grande importância quando se avalia a digestibilidade de um volumoso, pois à medida que se aumentam os seus valores, diminui-se a digestibilidade da MS (Branco et al, 2006). Pela interação Idade x Dose, observa-se que, na idade de 45 dias, houve um efeito quadrático do N sobre os valores de DIVMS e a dose que maximiza esta variável foi a de 313 mg/dm³ de N, correspondendo a 77,8%, ao passo que aos 65 dias detectou-se um efeito linear crescente do N sobre os coeficientes de DIVMS (Figura 6).…”
Section: Resultsunclassified
“…Rocha et al (2005) suggested that the relative chlorophyll content may be used as an indicator of nitrogen levels in the plant, in addition to providing a good correlation with the yield of some crops, such as Mombaça grass (Manarim & Monteiro, 2003) and Aruana grass (Lavres Júnior & Monteiro, 2006). The increase in the CP contents with higher doses of N may be explained by the presence of chlorophyll molecules in protein complexes and they are produced by the plant by the chloroplasts which possess RNA, DNA and ribosomes, thus being capable of synthesizing and multiplying proteins (Maranhão et al, 2009). The positive and high correlation between these attributes is of great importance in the early diagnosis of N deficiencies, ensuring that decisions are taken in good time for possible cover applications of this nutrient.…”
Section: Resultsmentioning
confidence: 99%